2004
DOI: 10.1002/chem.200400003
|View full text |Cite
|
Sign up to set email alerts
|

Organic Chlorine as a Hydrogen‐Bridge Acceptor: Evidence for the Existence of Intramolecular OH⋅⋅⋅ClC Interactions in Somegem‐Alkynols

Abstract: The acceptor capabilities of "organic" halogen, CX (X=F, Cl, Br, I), with respect to hydrogen bonding are controversial, and unactivated organic chlorine is generally deemed to be a poor acceptor. Hydrogen bridges of the type O--H...Cl--C are uncommon and occur mainly in an intramolecular situation when the donor group is sterically hindered, so that the formation of intermolecular interactions is difficult. In this paper, intramolecular O--H...Cl--C interactions in a series of chloro-substituted gem-alkynols … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 103 publications
2
47
0
Order By: Relevance
“…Intramolecular O-H⋅⋅⋅Cl hydrogen bond in 1-chloro derivatives of trans-9,10-diethynyl-9,10-dihydroanthracene-9,10-diols (DDA, figure 2) was confirmed by NMR spectroscopy and X-ray diffrac-tion. 8 The intramolecular O-H⋅⋅⋅Cl hydrogen bond (d = 2⋅25-2⋅40 Å) persisted in five out of six structures with varying number of Cl groups on the aromatic core. Of the two OH groups, the free OH resonates at δ 2⋅8 ppm in the NMR spectrum whereas the hydrogen bonded OH is significantly downfield at 4⋅4-4⋅6 ppm.…”
Section: Intermolecular Interactionsmentioning
confidence: 93%
“…Intramolecular O-H⋅⋅⋅Cl hydrogen bond in 1-chloro derivatives of trans-9,10-diethynyl-9,10-dihydroanthracene-9,10-diols (DDA, figure 2) was confirmed by NMR spectroscopy and X-ray diffrac-tion. 8 The intramolecular O-H⋅⋅⋅Cl hydrogen bond (d = 2⋅25-2⋅40 Å) persisted in five out of six structures with varying number of Cl groups on the aromatic core. Of the two OH groups, the free OH resonates at δ 2⋅8 ppm in the NMR spectrum whereas the hydrogen bonded OH is significantly downfield at 4⋅4-4⋅6 ppm.…”
Section: Intermolecular Interactionsmentioning
confidence: 93%
“…The nuclear magnetic resonance (NMR) and X-ray crystallographic studies have been reported on the N-H … F-C HB in foldamers and benzanilides 37,38 . It is also well known that organic fluorine generally does not get involved in the intramolecular HB [39][40][41][42][43][44][45] . The report by Dunitz and co-workers concluded that ''organic fluorine hardly ever accepts hydrogen bonds'' [46][47][48][49] .…”
Section: Introductionmentioning
confidence: 99%
“…That is to say, halogen atoms can form both a halogen bond with nucleophiles (electronegative atoms/groups) displaying roughly linear arrangement and a hydrogen bond with electrophiles (hydrogen bond donors) occurring in the side‐on fashion. The type of the interaction via side‐on mode is often referred to as hydrogen bonding or dipole interaction,43, 44 and the benchmark tests on some representative systems can be found in the literatures 45…”
Section: Introductionmentioning
confidence: 99%